RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN TERUNG UNGU (Solanum melongena L.) TERHADAP PEMBERIAN PUPUK FESES KELINCI DAN PUPUK NPK BOOS 324 - Siti Rahayu; Safruddin Safruddin; Deddy Wahyudin Purba (Universitas Asahan, 2020)
The study was conducted at the Experimental Garden of the Faculty of Agriculture, Asahan University, Kisaran Naga Village, Kota Kisaran Timur Subdistrict, Asahan Regency, North Sumatra Province with a flat topography and a height of ± 25 m above sea level, with sufficient water sources with sandy clay texture. The study was conducted in April to June 2018. This study was arranged based on Factorial Randomized Block Design (RBD) with two treatment factors and three replications, the first factor was the dose of rabbit feces fertilizer (K) consisting of 4 levels, namely K0 (without treatment), K1 (0.29 kg / plot) , K2 (0.58 kg / plot), and K3 (0.87 kg / plot), and the second fator is NPK BOOS 324 (N) fertilizer consisting of 3 levels namely N0 (control), N1 (10.8 g / plot), and N2 (21.6 g / plot). The results showed that the treatment of rabbit feces fertilizer had a significant effect on the growth and production of purple eggplant plants. The best treatment was at a dose of 0.87 kg / plot (K3) resulting in plant height of 53.26 cm, number of fruit 8.33 fruit, production per plant 1.13 kg and production per plot of 17.00 kg. NPK BOOS 324 fertilizer treatment significantly affected the growth and production of purple eggplant plants. The best treatment was found in the treatment of 21.6 g / plot (N2) resulting in the highest plant height of 53.26 cm, number of fruits of 8.00 fruit, production per plant of 1.00 kg and production per plot of 15.63 kg. The interaction of giving rabbit feces fertilizer and NPK BOOS 324 fertilizer did not show a significant effect on the growth of purple eggplant.